1985
DOI: 10.1111/j.1432-1033.1985.tb08916.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterisation of an odorant‐binding protein from cow nasal tissue

Abstract: Cow nasal tissue contains a protein which shows specific binding activity for ‘green’ smelling compounds such as 2‐isobutyl‐3‐methoxypyrazine. This protein has now been purified using anion‐exchange fast protein liquid chromatography. The protein has a relative molecular mass of 400000–44000, s= 3.1 ± 0.3 S, pI = 4.7 ± 0.1 with an absorbance maximum at 278 nm, and consists of two subunits with an identical relative molecular mass of 19000. It is localised in the soluble fraction of cells from the olfactory muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
87
1
2

Year Published

1990
1990
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(91 citation statements)
references
References 19 publications
1
87
1
2
Order By: Relevance
“…Compared to all sequenced lipocalins, the human and rat VEGPs show highest identity (45%) to the odorant binding protein I1 (OBP,,) identified in the rat lateral nasal gland (Dear et al, 1991;Bliiker et al, 1993). OBPs are abundant proteins in the nasal mucus covering the olfactory epithelium of several vertebrate species (Bignetti et al, 1985;Pevsner et al, 1988). They bind a broad range of structurally diverse hydrophobic odorant molecules but their specific physiological role is still unclear (Pelosi and Maida, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to all sequenced lipocalins, the human and rat VEGPs show highest identity (45%) to the odorant binding protein I1 (OBP,,) identified in the rat lateral nasal gland (Dear et al, 1991;Bliiker et al, 1993). OBPs are abundant proteins in the nasal mucus covering the olfactory epithelium of several vertebrate species (Bignetti et al, 1985;Pevsner et al, 1988). They bind a broad range of structurally diverse hydrophobic odorant molecules but their specific physiological role is still unclear (Pelosi and Maida, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The same uncertainty holds for the molecular characteristics of the complement to the odor stimulus, i.e., the odor receptor or, better stated, the reception processes. Biochemical studies have revealed the existence of an olfactory marker protein (OMP) (39,40), an odorant-binding protein (OBP) (6,48,49), and an olfactory specific G protein (G olf ) (35). The role of these proteins as well as that of adenylate cyclase as a possible second messenger in the olfactory transduction processes (46) is still the subject of study.…”
Section: Introductionmentioning
confidence: 99%
“…High binding activity of an OBP ligand has been found in nasal mucosal homogenates and minimal but variable binding activity in lung homogenates, implying that some may be present in the lung. 3 Although we found strong immunolabeling of OBP in tracheal and bronchial mucosal glands, we detected none in the bronchioles or alveoli. Our finding of scant expression in the airway surface epithelium has been noted by others and speculated to be artifact; 2,21 however, our finding of OBP mRNA in tracheal epithelial cultures confirms that low-level expression occurs.…”
Section: Discussionmentioning
confidence: 61%
“…Expression of OBP in bovine nasal glands is well documented; 2,3,21 however, the presence and function of OBP in the lung has not been characterized. High binding activity of an OBP ligand has been found in nasal mucosal homogenates and minimal but variable binding activity in lung homogenates, implying that some may be present in the lung.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation